Polyamorous thinking, monogamous terror: The defense of the traditional couple from Christian coordinates - Núñez Díaz, Víctor (Razón y fe, 2021)
The new models of affective relationships, cultivated in the heat of the postmodern tendency to resignify inherited social practices, have been promoting the popularization of “polyamory”. In the face of approaches that seek to de-hierarchize and broaden the framework of couple relationships, a brief review of the Christian conception of Love is offered here, in order to argue that the transcendent Christian experience of human affections provides a fuller and more meaningful experience of love than that contained in polyamorous conceptions.
Keywords: love; polyamory; meaning; monogamy; institution; commodification; bonds